Differential control of respiratory frequency and tidal volume during high-intensity interval training - Nicolo, A.; Marcora, S. M.; Bazzucchi, I.; Sacchetti, M. (Experimental Physiology, 2017)
Given that respiratory frequency (fR) has been proposed as a good marker of physical effort, furthering the understanding of how fR is regulated during exercise is of great importance. We manipulated recovery intensity and exercise duration during high-intensity interval training (HIIT) to test the hypothesis that fast inputs (including central command) contribute more than metabolic stimuli to fR regulation. Seven male cyclists performed an incremental test, a 10 and a 20 min continuous time trial (TT) as preliminary tests. Subsequently, recovery intensity and exercise duration were manipulated during HIIT (30 s work and 30 s active recovery) by performing four 10 min and one 20 min trial (recovery intensities of 85, 70, 55 and 30% of the 10 min TT mean workload; and 85% of the 20 min TT mean workload). The work intensity of the HIIT sessions was self-paced by participants to achieve the best performance possible. When manipulating recovery intensity, fR, but not tidal volume (VT), showed a fast response to the alternation of the work and recovery phases, proportional to the extent of workload variations. No association between fR and gas exchange responses was observed. When manipulating exercise duration, fR and rating of perceived exertion were dissociated from VT, carbon dioxide output and oxygen uptake responses. Overall, the rating of perceived exertion was strongly correlated with fR (r = 0.87; P < 0.001) but not with VT. These findings may reveal a differential control of fR and VT during HIIT, with fast inputs appearing to contribute more than metabolic stimuli to fR regulation. Differentiating between fR and VT may help to unravel the mechanisms underlying exercise hyperpnoea.